Melatonin Attenuates the Urea-Induced Yields Improvement Through Remodeling Transcriptome and Rhizosphere Microbial Community Structure in Soybean - Xiao, Renhao; Han, Qin; Liu, Yu; Zhang, Xuehai; Hao, Qingnan; Chai, Qingqing; Hao, Yongfang; Deng, Junbo; Li, Xia; Ji, Hongtao (Frontiers in Microbiology, 2022)
Foliar application of nitrogen to enhance crop productivity has been widely used. Melatonin is an effective regulator in promoting plant growth. However, the effects of melatonin and the combination of melatonin and nitrogen on soybeans yields production remain largely unknown. In this study, a field experiment was conducted to evaluate the effects and mechanisms of spraying leaves with melatonin and urea on soybeans. Foliar application of urea significantly increased soybean yields and melatonin did not affect the yields, while combination of melatonin and urea significantly reduced the yields compared to the application of urea alone. A leaf transcriptional profile was then carried out to reveal the underlying mechanism and found that foliar spraying of urea specifically induced the expression of genes related to amino acid transport and nitrogen metabolism. However, foliar application of melatonin significantly changed the transcriptional pattern established by urea application and increased the expression of genes related to abiotic stress signaling pathways. The effects of melatonin and urea treatment on soil microbiome were also investigated. Neither melatonin nor urea application altered the soil microbial alpha diversity, but melatonin application changed rhizosphere microbial community structure, whereas the combination of melatonin and urea did not. Melatonin or urea application altered the abundance of certain taxa. The number of taxa changed by melatonin treatment was higher than urea treatment. Collectively, our results provide new and valuable insights into the effects of foliar application of melatonin to urea and further show that melatonin exerts strong antagonistic effects on urea-induced soybean yields, gene expression and certain soil microorganisms.